2014
DOI: 10.1063/1.4897658
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the aluminum content on the shock wave pressure and the acceleration ability of RDX-based aluminized explosives

Abstract: To better understand the influence of the aluminum content on the performance of aluminized explosives, experiments in concrete and cylinder tests were performed. Three types of RDX-based aluminized explosives, in which the mass ratio of aluminum content was 0%, 15%, and 30% were considered in this paper. The shock wave pressures of the aluminized explosives in the affected concrete bodies were measured using manganin pressure sensors. The acceleration ability was obtained using a high-speed camera and a rotat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…The shock wave pressure P on the lower surface of the 1# plexiglas partition is measured using manganin pressure sensor, and the pressure on the upper surface of the 1# plexiglas partition is equal to the detonation pressure P DP of the test sample, so the detonation pressure P DP can be obtained according to attenuation law of shock wave pressure in plexiglass partition. The attenuation of the shock wave pressure versus distance is fit with a power-law function, as described in Equation (2) [24,25]. 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55…”
Section: Experimental Principles and Methodsmentioning
confidence: 99%
“…The shock wave pressure P on the lower surface of the 1# plexiglas partition is measured using manganin pressure sensor, and the pressure on the upper surface of the 1# plexiglas partition is equal to the detonation pressure P DP of the test sample, so the detonation pressure P DP can be obtained according to attenuation law of shock wave pressure in plexiglass partition. The attenuation of the shock wave pressure versus distance is fit with a power-law function, as described in Equation (2) [24,25]. 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55…”
Section: Experimental Principles and Methodsmentioning
confidence: 99%
“…Explosive charges were buried in concrete targets. The radius of the blasthole is 0.02 m. The concrete mixture used consists of cement, sand, crushed basalt and other components, as specified in Zhou et al [14]. The physical properties of the concrete are listed in Table 2.…”
Section: Aluminized Explosive Experiments In Concretementioning
confidence: 99%
“…In the concrete, Pei et al [13] performed explosion experiments with 70 g RDX-based aluminized explosive, the experimental results show that the damage area of RDX/Al/wax (80 %/15 %/5 %) is 10 % larger than pure RDX. Zhou et al [14] measured the shock wave pressures in the affected concrete bodies by using manganin pressure sensor, the results indicated that the pressure impulse of RDX/Al/wax (80 %/15 %/5 %) is 42 % higher than pure RDX. Aluminized explosives perform well in the concrete, but the role of aluminum reaction in the performance of RDX-based aluminized explosives in concrete has rarely been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…It is assumed that none of the aluminum particles reacted during the detonation, and the Al oxidation occurs in the products behind the detonation front. 15,16 For detonation of aluminized explosives, the duration for energy release of the reaction of explosive components is generally less than 0.1 ms, while the energy release for Al oxidation is in the order of microseconds to several milliseconds. 17 Therefore, the reaction rate of explosive components is much quicker than the rate of Al oxidation.…”
Section: The Reaction Mechanism Of Aluminized Explosivementioning
confidence: 99%